2007
DOI: 10.1038/sj.ejcn.1602804
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intake of B6-9-12 vitamins, serum homocysteine levels and their association with depressive symptoms: the Zutphen Elderly Study

Abstract: Our results do not support the hypothesis that a low dietary intake of B(6-9-12) vitamins and high levels of serum homocysteine are related to depression in healthy elderly men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
65
1
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 44 publications
(62 reference statements)
3
65
1
1
Order By: Relevance
“…There are a few possible reasons for the inconsistency. First, similar to studies showing no association with serum, plasma or red blood cell folate, the average age of subjects in three (Penninx et al, 2000;Tiemeier et al, 2002;Kamphuis et al, 2008) of the four studies with null finding exceeded 70 years. We thus infer that the association between homocysteine and depressive symptoms among the elderly may be lessened by serious diseases, which may have an adverse effect on mood.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…There are a few possible reasons for the inconsistency. First, similar to studies showing no association with serum, plasma or red blood cell folate, the average age of subjects in three (Penninx et al, 2000;Tiemeier et al, 2002;Kamphuis et al, 2008) of the four studies with null finding exceeded 70 years. We thus infer that the association between homocysteine and depressive symptoms among the elderly may be lessened by serious diseases, which may have an adverse effect on mood.…”
Section: Discussionmentioning
confidence: 77%
“…In the literature, their association has been inconsistent. Of nine studies, five observed an increased prevalence of depressive symptoms associated with a higher blood homocysteine concentration (Bjelland et al, 2003;Tolmunen et al, 2004b;Sachdev et al, 2005;Dimopoulos et al, 2007;Kim et al, 2008), but the others found no association (Penninx et al, 2000;Tiemeier et al, 2002;Morris et al, 2003;Kamphuis et al, 2008). There are a few possible reasons for the inconsistency.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Secondly, a less than optimum supply of micronutrients, especially of some B vitamins, is associated with a higher risk of depressive symptoms (143,144). Thirdly, even a moderate micronutrient deficit will compromise the immune competence of the organism (145,146), as immune cells, due to their high proliferation rate, have an increased nutrient need.…”
Section: Tumor-associated Deficit Of Micronutrients -Pathophysiologicmentioning
confidence: 99%